RESTORATIVE JUSTICE DALAM PENANGANAN PERKARA KELALAIAN MEDIS: ALTERNATIF PEMIDANAAN BERBASIS PERLINDUNGAN PASIEN - Dita Rosalia Arini; Uta Provinsiana Sukmara (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The handling of medical negligence cases in the criminal justice system often creates tension between efforts to protect patients' rights and the risk of criminalization of medical personnel. Conventional penalty-oriented approaches are considered not to be fully able to provide substantive justice, both for patients and medical personnel, and have the potential to encourage the practice  of defensive medicine. This study aims to analyze the urgency of the application of restorative justice as an alternative to punishment in medical negligence cases oriented towards patient protection and professional accountability of medical personnel. The research method used is normative legal research with a legislative, conceptual, and case approach, through an analysis of the provisions of criminal law, health law, and restorative justice-based law enforcement policies. The results of the study show that the application of restorative justice in medical negligence cases allows the realization of the restoration of patients' rights more quickly and proportionately, while preventing excessive criminalization of medical personnel, as long as they meet strict material and formal requirements. This study concludes that restorative justice is a relevant and contextual approach to be developed in the Indonesian criminal justice system to realize a balance between patient protection, legal certainty, and substantive justice.